Analisis dan Perbaikan Tata Letak Proses Verifikasi Data Tagihan untuk Meningkatkan Efisiensi Kerja di PDAM - Nur Qidam Aliyanto; Naufal Nur Alfian; Mukhamad Kurniawan; Ida Kusnawat Tjahjani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Perusahaan Daerah Air Minum is a regional public utility company that has implemented digital information systems to manage customer data, including the billing data verification process. Despite this digital adoption, the current verification workflow still contains a high proportion of Non-Value Added (NVA) activities due to the absence of automated error filtering, system integration, and manual data copying. This study aims to: (1) map the existing billing verification workflow using a Flow Process Chart (AS-IS); (2) quantify value-added (VA) and non-value-added (NVA) activities and calculate process efficiency; and (3) propose an improved process layout (TO-BE). Data were collected through direct observation of 2,110 customer records during an internship at PDAM. Results show that of seven workflow steps, only two (28.6%) are VA activities, while five (71.4%) are NVA. Time-based Process Efficiency of 58.5% falls below the lean ideal of 60–70%. Proposed improvements—including system integration, auto-fill functionality, and automatic error filtering—are projected to reduce verification time per record by 50–60% and raise the VA ratio to 75%.